A cross-sectional study of how high-frequency hearing loss impacts cognitive functions in middle-aged-to-older adults - Jayakody, Dona M. P.; McIlhiney, Paul; Stegeman, Inge; Eikelboom, Robert H. (Frontiers in Aging Neuroscience, 2025)
PurposeResearch on the association between hearing loss and cognition has primarily focused on speech-range hearing frequencies (i.e., 0.5–4 kHz), as these frequencies are most relevant to everyday functioning. However, age-related hearing loss (ARHL) tends to impact higher-frequency hearing first, and more severely. Despite this, limited research has investigated the relationship between high-frequency (i.e., >4 kHz) hearing loss and cognitive impairment. In the current study, we aimed to assess whether high-frequency hearing loss predicts non-verbal cognitive functions (i.e., visuospatial executive function, learning, and memory tasks) above and beyond speech-frequency hearing loss.Materials and methodsParticipants were 241 English-speaking adults, aged 40–88 years, with hearing loss. Audiometrically assessed better-ear, speech-frequency (0.5, 1, 2 & 4 kHz; BE4PTA) and high-frequency (6 & 8 kHz; BE2PTA) hearing loss were compared to cognitive functions measured using non-verbal tests from the Cambridge Neuropsychological Test Automated Battery; covariates included hearing-loss asymmetry, age, sex, premorbid IQ, and mental health measured with the short-form Depression Anxiety Stress Scales.ResultsWhile correlation analyses demonstrated that all measured cognitive faculties were associated with both BE4PTA and BE2PTA, hierarchical linear regression analyses demonstrated that only BE4PTA predicted cognitive flexibility and working-memory ability after controlling for covariates; age primarily accounted for BE2PTA’s cognitive effects.ConclusionWhile both speech and higher-frequency hearing loss were associated with poorer cognition, only the former demonstrated effects beyond those of ageing. However, the present study only investigated two frequencies in the higher range, encouraging broader investigation of higher-frequency hearing’s cognitive effects in the future.